Can Lambs in Pain Identify Medicated Feed? - Marini, Danila; Colditz, Ian G.; Lee, Caroline (Frontiers in Animal Science, 2021)
Lambs in Australia undergo painful husbandry procedures as part of common husbandry. The magnitude and duration of pain are difficult to assess in lambs. Most currently used methods rely on behavioral expressions and physiological markers that may fail to detect the state of pain an animal experience. This study examined motivation of 12-week-old lambs experiencing chronic pain to self-medicate by consumption of feed containing an analgesic agent as an indicator of pain in lambs. In this study, 36 male Merino lambs were individually penned and acclimated to pelleted feed and two artificial odors: strawberry and banana. Once acclimated to odored feed, lambs were tested for their individual preference for the odors. Lambs were then assigned to one of two groups: Sham – sham handled day 0 and 7 or Ring – Ring castrated day 0 and tail docked day 7. To enable self-medication testing, lambs underwent a conditioning period (day 0 – 3) followed by the self-medication period (day 7 - 12). On day 0 lambs were castrated or sham handled, and then offered only medicated feed that contained an odor cue (either strawberry or banana). On day 7, lambs underwent tail-docking or sham handling and were offered both the conditioned medicated feed and non-medicated feed. Amount of feed consumed was recorded 1 and 12 h after offer each day. Blood samples were taken for cortisol and white blood cell analysis and behavioral observations were recorded for 12 h following treatment. There was no difference in preference for medicated feed between Ring and Sham lambs during the self-medication phase (P = 0.18). Lambs in both groups displayed a significant preference for strawberry cued medicated feed during the self-medicated period when compared to the other testing periods (P = 0.05). Ring lambs displayed more active pain behaviors (mean = 15.1) than Sham (mean = 0.4, P < 0.05). Following castration, Ring lambs had a higher neutrophil/lymphocyte ratio at 6, 24, 48 and 72 h. This study was not able to demonstrate that lambs can self-medicate for a state of pain.